COVID-19 pandemic experiences of students from BAME and White ethnic groups pursuing higher education in the UK: A qualitative comparative exploration - Hitch, Geeta; Zaman, Shahaduz (Frontiers in Psychiatry, 2023)
Abstract Background: The new severe acute respiratory syndrome coronavirus 2, SARS-Cov2, more commonly known as COVID-19 continues to be an ongoing cause of one of the most disruptive pandemics worldwide. Students at UK universities come from different backgrounds and cultures and the majority returned home or lived alone during the lockdown. The aim of this qualitative study was to compare the experiences of students from Black, Asian and Minority Ethnic (BAME) backgrounds and the White British students. Method: An in depth interview was conducted with each one of the thirty-five students, 18 from BAME and 17 from White backgrounds, respectively, on Zoom or Microsoft Teams in their homes between November 2020 until May 2021. Interview transcripts were checked for accuracy and were analysed using N-Vivo coding software for themes. Data were collected on students’ pre-pandemic and during pandemic experience including perceptions of the COVID-19 virus, physical environment in which students lived and the effect on their general wellbeing, social interactions and online learning, teaching and assessment. Results: Mental health issues were more prevalent amongst female students compared to males and that this was more evident amongst BAME females who had returned to living at home, possibly due to lack of personal space. There was a reduction in personal hygiene in White females. There was an increase in the use of social media, particularly by BAME females. Students mostly disliked online learning and exams. Concerns were also raised about how universities communicated important information to the students. Conclusion: Based on the recommendations of the WHO in relation to COVID-19, universities need to effectively manage the information they provide to students and build trust through risk communication and community engagement. One important area in this regard is addressing access to mental health services. The reasons why BAME females experience more mental health issues should be explored further.